Pressure-Related Universal Previtreous Behavior of the Structural Relaxation Time and Apparent Fragility - Aleksandra Drozd-Rzoska (Frontiers in Materials, 2019)
The report presents the evidence for the hypothetically “universal” previtreous behavior of the pressure related apparent fragility: mT(P)∞1/(P*-P), where P* is the extrapolated singular pressure. This finding was the basis for deriving the “model-free” dependence for the pressure evolution of the structural relaxation time: τ(P)=τoP(P*-P)-Ψ. All these led to the new way of testing the dynamic crossover phenomenon via 1/mT (P) vs. P plot. Finally, the behavior of electric conductivity in the previtreous domain is discussed. The experimental evidence covers 8*OCB (liquid crystal), EPON 828 (resin), diisobutyl phthalate, and propylene carbonate (low molecular weight liquids). Experiments were carried up to extreme P~ 2.2 GPa, in the “bulk” measurement capacitor. This report also contains a summary of existing descriptions of the pressure evolution of structural relaxation time or viscosity on approaching the glass transition.